The Relationship between Optimism, Pre-Entrepreneurial Curiosity and Entrepreneurial Curiosity - Jeraj Mitja (Organizacija, 2014)
Background: Entrepreneurship and entrepreneurs become more and more interesting fields for a scientific research. This paper addresses the relationship between optimism, pre-entrepreneurial curiosity and entrepreneurial curiosity as three determinants of entrepreneurial psychology. Literature review showed optimism is important for entrepreneurs and influence them mostly in a positive way. Although entrepreneurial curiosity is important determinant for entrepreneurs and it was connected with entrepreneurial self-efficacy, openness, and company's growth the connection with optimism remained unexplored until this research.